Wisata Halal untuk Mencapai Pembangunan Ekonomi Masyarakat Desa dan Tujuan Maqashid Syariah (Studi Kasus pada Desa Wisata Pujon Kidul, Kabupaten Malang, Jawa Timur) - Ahsani Taqwiem; Ahmad Rofiq Zakariya (El-Aswaq, 2020)
Nowadays, halal tourism with economic community empowerment beinggoverment concentration in advancing the economy in Indonesia. Asset basedcommunity development is one of the method approach on empowering theeconomic community. Then, village assets such as nature, humans, and otherresources become a potential empowerment and welfare of the villagecommunity.Pujon Kidul as one of the tourism village destination has the both element :residents and village officials participated in the development and empowermentof the village community, is in line with Islamic principles, namely maqashidSyari’ah. This study exerts a qualitative approach with case study on Pujon Kidultourism village. Data from this study were obtained by conducting observations,interviews, and documentation.While the data were analyzed by triangulation method to determine thevalidity of the data obtained. Through this research, it was found that halaltourism development im Pujon Kidul village has a great strategy to build thevillage, as like the role of government of keeping al-Dharuriyat, industry sectorwhich can be material, financial, or empowerment training and private industry asfor keeping al-Hajjiyat, and maintaining tahsiniyat by using mass media to supportpromotional activities..